2021
DOI: 10.3390/toxics9110310
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate Esters in China: Fate, Occurrence, and Human Exposure

Abstract: Organophosphate esters (OPEs) are widely used as flame retardants and plasticizers. OPEs have been released into various environments (e.g., water, sediments, dust and air, and soil). To investigate the occurrence and distribution of OPEs in various environments in China, this review collects and discusses the published scientific studies in this field. Chlorinated OPEs, as flame retardants, are the predominant OPEs found in the environment. The analysis of data revealed large concentration variations among mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 108 publications
(266 reference statements)
2
18
0
Order By: Relevance
“…As shown in Figure S6, most OPFRs were mainly apportioned to this source in PMF, especially for TCEP, TCPP, EHDPP, and TnBP. TCPP and TPHP are mainly applied in polyurethane foam; , EHDPP is primarily used in food packaging, paints, and rubber, , while TMPP and TBOEP are used in abandoned automobiles and electric wires . Like our results, Wang et al also found waste recycling as an important source of environmental chlorinated- and aryl-OPFRs by measuring dust and soil samples collected from a waste recycling area.…”
Section: Results and Discussionsupporting
confidence: 83%
“…As shown in Figure S6, most OPFRs were mainly apportioned to this source in PMF, especially for TCEP, TCPP, EHDPP, and TnBP. TCPP and TPHP are mainly applied in polyurethane foam; , EHDPP is primarily used in food packaging, paints, and rubber, , while TMPP and TBOEP are used in abandoned automobiles and electric wires . Like our results, Wang et al also found waste recycling as an important source of environmental chlorinated- and aryl-OPFRs by measuring dust and soil samples collected from a waste recycling area.…”
Section: Results and Discussionsupporting
confidence: 83%
“…However, 1000 is the most commonly used factor when acute toxicity value is used [63]. PNEC is often determined using Equation ( 2) [31,64,65].…”
Section: Risk Assessment Of Opfrsmentioning
confidence: 99%
“…This assessment result could vary from low risk to high risk to the aquatic organisms in such an environment. Low risk is implied by 0.01 < RQ < 0.1; moderate risk by 0.1 < RQ < 1 and high risk by RQ > 1 [56,[65][66][67][68][69]. Table 3 shows some PNECs for OPFRs in different environmental matrices.…”
Section: Risk Assessment Of Opfrsmentioning
confidence: 99%
“… 19 21 As a substitute for polybrominated diphenyl ethers, organophosphate esters (OPEs) are commonly used as flame retardants and plasticizers, 22 and the global annual consumption of OPEs exceeded 680,000 tons in 2015, with 30% of the usage was reported in China. 23 As a result, OPEs are ubiquitously detected in Chinese individuals in the microgram to milliliter range. 24 Such high OPE exposure levels adversely impact the reproductive, endocrine, cardiovascular, and nervous systems.…”
Section: Introductionmentioning
confidence: 99%